MANUSKRIP OPTIMALISASI UNIT DIKYASA MELALUI PROGRAM POLICE GO TO SCHOOL GUNA MENGURANGI ANGKA KECELAKAAN LALU LINTAS DI KALANGAN PELAJAR SMA - wibowo, Rizky akbar (Advances in Police Science Research Journal, 2020)
The high number of traffic accidents that occur among high school-aged teenagers in Garut district receives special attention from Garut Regional Police who have the main task of protecting, protecting and serving the community. To overcome these problems, the Unit of Satlantas Garut Police Precinct took a preventive effort by carrying out public education / public education about traffic through the Police go to school method. This study aims to obtain an overview of the implementation of Dikmas then through the Police go to school method and to obtain an overview of the role of Dikyasa Unit personnel in reducing the number of traffic accidents among high school students in the Garut Police jurisdiction as well as the factors that influence the implementation of the Dikmas then through the method Police go to school. This thesis research is a research with a qualitative approach, the type of research is analytical descriptive. The sources of this research data are primary data sources and secondary data sources. Then, the data collection techniques used in writing this thesis are observation, interview, and document study. Furthermore, to test the accuracy and accuracy of the data in this study using triangulation techniques. Data analysis techniques in qualitative research are data reduction, data presentation, and drawing conclusions. The results showed that the Dikmas then with the Police go to school method implemented by the Garut Satlantas Unit of the Garut Regional Police Precinct were not optimal, this was influenced by the lack of the number of Dikyasa Unit personnel and the qualifications of the community education sector which were judged to be still low and the low interest and participation of high school students in participating Dikmas activities then. So it needs optimization in the implementation of community education then in the future.